Development of Teaching Props on Water Cycle in Fifth Class Madrasah Ibtidaiyah - Mukaromah, Siti; Supriatin, Atin; Syar, Nur Inayah (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2023)
The research and development of teaching aids was motivated by the fact that students in class V MIN 1 in Palangka Raya City were faced for the past 2 years with online learning, some of which had an impact on decreasing learning outcomes, lack of student interest in learning, and the need for additional creative teaching aids to arouse students' interest in learning. . Teaching aids are communication tools used by teachers in the learning process. Having valid teaching aids will make it easier for students to understand the material. On the other hand, if the props used are not valid then it will not facilitate understanding for the participants. This development aims to describe the development of teaching aids for class V water cycle material at MI, and to determine the feasibility of the results of developing teaching aids for class V water cycle material at MI. This research is a type of Research and Development (R&D) research that uses the 4- D model. Data collection uses interview, observation, documentation and questionnaire techniques. The final results of this research showed that the validity test of media experts' teaching aids obtained a percentage score of 97.91%, and material experts obtained a percentage score of 98.21%, in the category of very valid and suitable for use. The student response to the results of developing teaching aids was 95.83%.